Study and performance analysis of charging vehicle battery using bike exhaust gas - Kumaravel, K.; Balashanmugam, P.; Balasubramanian, G. (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
Nowadays, the environment as well as their dwellers surviving here have recently been badly influenced by one of the most burning problems, i.e. ‘Air pollution, which is caused due to emission of toxic exhaust into the sounding resulted, running the floral and faunal lives. Generally, these toxic gases emit from vehicle exhaust, power plants, small and large scale industries and mixed into atmospheric air and increased the pollution rate. In recent years an increasing concern of environmental issues of emission in particular global warming and the limitations of energy resources has resulted the extensive research in naval technology of generating electrical power. In this study of electrical power generation using IC engines exhaust gas and performance analysis was conducted by presenting the charging vehicle battery by using bike exhaust gas. The experimental investigation shows get converted into how the exhaust gases were utilized and kinetic energy from mechanical energy and further converted it into AC current resulting electrical power generation. The result indicates the electrical power generated by the exhaust gas of IC engine was successfully observed.